Drowitch - FRATINI, Erich Alves; SILVA, Lucas de Souza Silva; BARRETO, Tatiane Lucia de Souza; ALBUQUERQUE, Victor Rocha de; OLIVEIRA, Vitor Dalessi de (172, 2016)
O Drowitch é um drone do tipo overland(terrestre) equipado com uma camera em tempo real. Ele é capaz de identificar inimigos e reconhecer a area no qual anda.

The Drowitch is an overland (terrestrial) type drone equipped with a realtime camera. He is able to identify enemies and recognize the area in which he walks. Key words: Ethics, Freedom, Perseverance and Respect.
Keywords: Ética; Informação e Comunicação